A qualitative study of talent identification and selection in youth soccer: talent scouts` perceptions - Steenbok, W.; Morris-Eyton, H.; Kubayi, A. (The Journal of Sports Medicine and Physical Fitness, 2026)
BACKGROUND: This study explored the perceptions of talent scouts regarding the attributes they consider essential when identifying talented youth soccer players.